2000
DOI: 10.1002/(sici)1099-1263(200001/02)20:1<35::aid-jat633>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The peripubertal male rat assay as an alternative to the Hershberger castrated male rat assay for the detection of anti-androgens, oestrogens and metabolic modulators

Abstract: A range of chemicals with various levels of activity as actual or potential endocrine disrupters have been evaluated for activity in the peripubertal male rat assay. The chemicals studied included anti‐androgens (vinclozolin), cyproterone acetate, flutamide, 2,2‐bis(4‐chlorophenyl)‐1,1‐dichloroethylene (DDE), metabolic modulators (anastrazole, finasteride, ketoconazole) and oestrogens (butyl benzyl phthalate (BBP), methoxychlor, bisphenol A (BPA), diethylstilboestrol (DES)), the suspected anti‐androgen dibutyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(28 citation statements)
references
References 35 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Antiandrogenic compounds so far reported include vinclozolin, linuron, iprodione, chlozolinate, procymidone, flutamide, p,p´-DDE, and ketoconazole (Gray et al 1999a(Gray et al , 1999bLambright et al 2000;McIntyre et al 2000;Ostby et al 1999;You et al 1999). In contrast, both positive and negative results on the antiandrogenic activity of fenitrothion, a relative of fenthion, have been reported (Ashby and Lefevre 2000;Curtis 2001;Sohoni et al 2001;Sunami et al 2000;Tamura et al 2001). The significant antiandrogenic activity of fenitrothion found in our study supports previous findings that fenitrothion has antiandrogenic properties.…”
Section: Discussionmentioning
confidence: 80%
“…Antiandrogenic compounds so far reported include vinclozolin, linuron, iprodione, chlozolinate, procymidone, flutamide, p,p´-DDE, and ketoconazole (Gray et al 1999a(Gray et al , 1999bLambright et al 2000;McIntyre et al 2000;Ostby et al 1999;You et al 1999). In contrast, both positive and negative results on the antiandrogenic activity of fenitrothion, a relative of fenthion, have been reported (Ashby and Lefevre 2000;Curtis 2001;Sohoni et al 2001;Sunami et al 2000;Tamura et al 2001). The significant antiandrogenic activity of fenitrothion found in our study supports previous findings that fenitrothion has antiandrogenic properties.…”
Section: Discussionmentioning
confidence: 80%
“…As shown in Table 8, with the exception of early balano-preputial separation after exposure to phthalates (Ge et al, 2007;Saillenfait et al, 2008), EDCs appear to cause either no effect or a delay of sexual maturation in the male rodent. BPA does not show any effect whatever the dose and the window of exposure (Tinwell et al, 2002;Nagao et al, 1999;Tan et al, 2003;Ashby and Lefevre, 2000). As shown in Fig.…”
Section: Endocrine Disrupters and Timing Of Puberty: Mechanisms Of Acmentioning
confidence: 99%
“…Although both fetal and early postnatal periods of exposure fall into the so-called "programming window", there may be differences in sensitivity to endocrine disruption even within this particular period. The dose of EDC plays a critical role since, when investigated at a given period of life, higher doses appear to be more effective such as shown after prenatal exposure for DDE (Loeffler and Peterson, 1999) and phthalates (Saillenfait et al, 2008;Salazar et al, 2004), or after lactational exposure for DDE, vinclozolin or DES (Yoshimura et al, 2005) or following exposure after weaning for DDE (Ashby and Lefevre, 2000;Yoshimura et al, 2005), vinclozolin (Yoshimura et al, 2005;Monosson et al, 1999), DES (Yoshimura et al, 2005;Shin et al, 2009), phthalates (Ge et al, 2007;Noriega et al, 2009) and PBDE (Stoker et al, 2004). It is noteworthy that in two studies using phthalates, opposing effects are observed since lower doses are associated with early puberty and higher doses with delayed puberty (Ge et al, 2007;Saillenfait et al, 2008).…”
Section: Endocrine Disrupters and Timing Of Puberty: Mechanisms Of Acmentioning
confidence: 99%
“…P,pЈ-DDE exposure in "foreign-born" girls was associated with earlier puberty relative to native-born Belgians 99 and, possibly, increasing DDE in utero exposure with earlier puberty in girls 97,98 ; however, no animal studies of DDE exposure and female puberty timing were identified, limiting additional interpretation of the human data. In male rats, peripubertal DDE exposure delays PPS, [116][117][118] although no relation to lower exposures was found in boys after in utero DDE exposure. 97 The weight of animal and human data, although suggestive, remains inconclusive for establishing a causal relation between EDCs and human pubertal disturbances.…”
Section: Cross-species Concordance Of Pubertal Timing Effectsmentioning
confidence: 99%